Shakespeare reciclado : uma adapação cinematográfica de A megera domada no filme 10 coisas que eu odeio em você - Carvalho, Luana Melissa de (2015)
This study analyses the Shakespearean theater screen adaptation, specifically the work The Taming of the Shrew, into the film 10 Things I Hate About You, through an intersemiotic translation reflection inspired by Peirce's sign definitions and understood as a form of creative hypertextuality. The study addresses the dialogical relations between the source text and its hypertext, considering their respective contexts. It is discussed the issues related to adaptation and appropriation (considering that cinema, as a mean of art reproduction, appears as one of the most effective ways of adaptation - literary or otherwise), which bring out questions about Shakespeare’s perpetual canonicalization or its resistance under the terms of recycling. It was also discussed the intermediality concept as an essential form of medium for the rereadings done so far.